THE EFFECT OF USING DRAMA TECHNIQUE TOWARDS STUDENTS’ SPEAKING SKILL - Irliani Juwita Zahri; Putri Asilestari (Universitas Muhammadiyah Ponorogo, 2022)
This experimental research was conducted in class X at SMAN 1 Bangkinang. The purpose of this research is to find out the effect of using drama technique towards students’ speaking skills. This research methodology uses a Quasi-Experimental design. The sample of this research is class XA as the experimental class with 29 students and class XB as the control class with 28 students. This research used a random sampling technique involving class X. The instrument used in this research was a speaking skills test. Data analysis using the SPSS version 24 program. Based on the results of the study, the average score of students in the experimental class was 69.38 and the average score in the control class was 34.00. Data analysis showed significant (2-tailed) 0.0000.05. This means that Ha is accepted. So, it can be concluded that drama technique has a good effects on students’ speaking skills.